Model of extensive and severe tracheal stenosis in dogs - Vaidergorn,Jairo (2008)
PURPOSE: To create an animal model of extensive longitudinal tracheal stenosis (TS) that can be useful to test different surgical techniques of tracheal reconstruction. METHODS: Twenty male mongrel dogs were submitted to standard TS and randomly distributed to observation for 3 weeks (n=10) or 6 weeks (n=10). Under general anesthesia, an elliptical area (major axis from 1st to 20th ring and minor axis 40% of tracheal diameter) was resected and the stumps were sutured. The internal and external diameters were measured (before and after the observation time) and the stenosis index was calculated. Blood samples were collected (gasometry, hematocrit and hemoglobin.) before and after the surgical proceedings. RESULTS: The weight was significant lower in the animals of 6 weeks (15,551±3286.2) in comparison with those of 3 weeks observation (17,250±3575.0). No significant differences were noted in the extension of the trachea on the 21st day (21.2± 1.8) or 42nd day (21.1±1.7). The mean (40.1) and the median (40.5) of rings counted on the 21st day were quite similar to mean (38.1) and median (39.0) that were counted on the 42nd day. In the animals of group A (3 weeks) the mean (46.8%) and the median (49.8%) of index stenosis showed no significant difference (Mann Whitney test p<0.001) in comparison with the mean (55.1%) and median (52.4%) of the animals from group B (6 weeks). No mechanical or biochemical distresses were recorded through all period of observation. CONCLUSION: The surgical proceeding was effective to promote a model of longitudinal and extensive tracheal stenosis.